Single-cell RNA sequencing reveals a novel inhibitory effect of ApoA4 on NAFL mediated by liver-specific subsets of myeloid cells - Liu, Xiao-Huan; Zhou, Jin-Ting; Yan, Chun-xia; Cheng, Cheng; Fan, Jing-Na; Xu, Jing; Zheng, Qiangsun; Bai, Qiang; Li, Zongfang; Li, Shengbin; Li, Xiaoming (Frontiers in Immunology, 2022)
The liver immune microenvironment is a key element in the development of hepatic inflammation in NAFLD. ApoA4 deficiency increases the hepatic lipid burden, insulin resistance, and metabolic inflammation. However, the effect of ApoA4 on liver immune cells and the precise immune cell subsets that exacerbate fatty liver remain elusive. The aim of this study was to profile the hepatic immune cells affected by ApoA4 in NAFL. We performed scRNA-seq on liver immune cells from WT and ApoA4-deficient mice administered a high-fat diet. Immunostaining and qRT–PCR analysis were used to validate the results of scRNA-seq. We identified 10 discrete immune cell populations comprising macrophages, DCs, granulocytes, B, T and NK&NKT cells and characterized their subsets, gene expression profiles, and functional modules. ApoA4 deficiency led to significant increases in the abundance of specific subsets, including inflammatory macrophages (2-Mφ-Cxcl9 and 4-Mφ-Cxcl2) and activated granulocytes (0-Gran-Wfdc17). Moreover, ApoA4 deficiency resulted in higher Lgals3, Ctss, Fcgr2b, Spp1, Cxcl2, and Elane levels and lower Nr4a1 levels in hepatic immune cells. These genes were consistent with human NAFLD-associated marker genes linked to disease severity. The expression of NE and IL-1β in granulocytes and macrophages as key ApoA4 targets were validate in the presence or absence of ApoA4 by immunostaining. The scRNA-seq data analyses revealed reprogramming of liver immune cells resulted from ApoA4 deficiency. We uncovered that the emergence of ApoA4-associated immune subsets (namely Cxcl9+ macrophage, Cxcl2+ macrophage and Wfdc17+ granulocyte), pathways, and NAFLD-related marker genes may promote the development of NAFL. These findings may provide novel therapeutic targets for NAFL and the foundations for further studying the effects of ApoA4 on immune cells in various diseases.